Steady-state and time-resolved studies on the photophysical properties of fullerene-pyropheophorbide a complexes in polar and nonpolar solvents - Ermilov, Eugeny; Al-Omari, S.; Helmreich, Matthias; Jux, Norbert; Hirsch, Andreas; Röder, Beate (Optics Communications, 2004)
A novel monofullerene-bis(pyropheophorbide a) dyad has been photophysically characterized by steady-state as well as time-resolved techniques. It was revealed that in this complex strong and fast quenching of the first excited singlet state of the pyropheophorbide a (pyroPheo) molecule occurs by efficient photoinduced electron transfer to the fullerene moiety in both polar (DMF) and nonpolar (toluene) solvents. In DMF the energy of the charge-separated state is 0.94 eV and it undergoes directly transition to the ground state resulting in a very low value of photosensitized singlet oxygen generation. In contrast to the situation in a polar solvent, in toluene the charge-separated state lies above the exited triplet state of pyroPheo as well as that of C. It has been shown that in a nonpolar solvent a sufficient amount of singlet oxygen was generated by energy transfer from the excited triplet state of pyroPheo which has been populated via relaxation of the charge-separated state. © 2004 Elsevier B.V. All rights reserved.